The Influence of Western Laws on Japanese Laws and Implications for Vietnam - Thang, Mai; Doan, Hoang Van (VNU Journal of Science: Legal Studies, 2018)
This article explores the effects of Western laws on Japanese laws from a legal history perspective. Thereby, the authors clarify the ways of integrating foreign law and decode the choices, decisions of the Japanese government. This paper also analyzesthe areas of the Japanese legal system that have been affected by the Western law as well as clarifies the factors of foreign law integration and reasons for the success of the Japanese legal system in integrating laws from different Western legal systems as well as in combining traditional Japanese elements with extrinsic progress values. There from, valuable experiences are drawn for Vietnam in building and completing its current legal system. Keywords: Influence of law, Western law, Japanese law, history of law, Vietnamese law.